UPAYA HUKUM TERHADAP TIONGKOK ATAS TINDAKAN PELARANGAN PELAYARAN KAPAL DI PERAIRAN KEPULAUAN SPRATLY PASCA PUTUSAN PERMANENT COURT OF ARBITRATION KASUS FILIPINA-TIONGKOK - NIM. A1011191115, VICHELLE (Jurnal Fatwa Hukum, 2025)
AbstractThe South China Sea with all its advantages has caused disputes between surrounding countries, one of which is the dispute between the Philippines and China which is still ongoing today. The Philippines and China are fighting over the Spratly Islands, located in the South China Sea, which are located between the waters of the two countries. China claims the Spratly Islands on historical grounds, while the Philippines claims them due to their geographical proximity. After the Permanent Court of Arbitration (PCA) ruling that the Spratly Islands are the sovereignty of the Philippines, China committed various violations against the Philippines. This study aims to provide legal remedies against China for the act of banning ship shipping in the waters of the Spratly Islands after the PCA Decision in the Philippines and China case. This study uses a type of normative legal research with a literature study method supported by international legal theories that use international legal sources. By using qualitative analysis techniques that will produce descriptive data, the analysis will be used by the author in conveying the author's views on the steps that should be taken and the legal remedies that should be given for the actions that have occurred. The result of this study is that after the Permanent Court of Arbitration (PCA) ruling that the Spratly Islands are the sovereignty of the Philippines, China rejected the decision and continued to claim the Spratly Islands territory as its own. China committed various violations by threatening Philippine vessels passing through the waters of the Spratly Islands, such as firing laser weapons, and carrying out other prohibitions. Although China does not accept the PCA's ruling, the PCA's ruling remains valid and binding. The Philippines can sue China through the International Court of Justice (ICJ) and the International Tribunal for the Law of the Sea (ITLOS).Keywords: Dispute; Philippines; China; Spratly Island; Permanent Court of ArbitrationAbstrak Laut China Selatan dengan segala kelebihannya menyebabkan terjadinya sengketa antar negara-negara disekitarnya, salah satunya sengketa antara Filipina dan Tiongkok yang masih berlangsung hingga kini. Filipina dan Tiongkok saling memperebutkan Kepulauan Spratly yang terletak di Laut China Selatan yang letaknya berada di antara perairan kedua negara. Tiongkok mengklaim Kepulauan Spratly berdasarkan alasan sejarah, sementara Filipina mengajukan klaim karena kedekatannya secara geografis. Setelah adanya putusan Permanent Court of Arbitration (PCA) yang memutuskan bahwa Kepulauan Spratly merupakan kedaulatan Filipina, Tiongkok melakukan berbagai pelanggaran terhadap Filipina. Penelitian ini bertujuan untuk memberikan upaya hukum terhadap Tiongkok atas tindakan pelarangan pelayaran kapal di perairan Kepulauan Spratly Pasca Putusan PCA kasus Filipina dan Tiongkok. Penelitian ini menggunakan jenis penelitian hukum normatif dengan metode studi kepustakaan yang didukung dengan teori hukum internasional yang menggunakan sumber hukum internasional. Dengan menggunakan teknik analisis kualitatif yang akan menghasilkan data deskriptif analisis yang akan digunakan penulis dalam menyampaikan pandangan penulis mengenai langkah-langkah yang seharusnya dilakukan dan upaya hukum yang seharusnya diberikan atas tindakan yang telah terjadi. Hasil dari penelitian ini adalah setelah adanya putusan Permanent Court of Arbitration (PCA) yang memutuskan bahwa Kepulauan Spratly merupakan kedaulatan Filipina, Tiongkok menolak keputusan tersebut dan tetap mengklaim wilayah Kepulauan Spratly sebagai miliknya. Tiongkok melakukan berbagai pelanggaran dengan mengancam kapal-kapal Filipina yang melintas di perairan Kepulauan Spratly, seperti menembakkan senjata laser, dan melakukan pelarangan lainnya. Meskipun Tiongkok tidak menerimakeputusan PCA, putusan PCA tetap sah dan mengikat. Filipina dapat menuntut Tiongkok melalui Mahkamah Internasional (ICJ) dan Mahkamah Internasional Hukum Laut (ITLOS).Kata Kunci : Sengketa; Filipina; Tiongkok; Kepulauan Spratly; Permanent Court of Arbitration